Выбор рациональных режимов отпуска теплоты теплофикационными блоками ТЭЦ - Шубенко, Александр Леонидович; Лыхвар, Н. В.; Зализняк, О. А. (НТУ "ХПИ", 2006)
Розглядається технологія розв’язання задач оптимізації режимів ТЕЦ з використанням гнучких моделей енергоустановок, що адаптуються до конкретної ситуації. Проведено розрахункові дослідження режимів відпуску теплоти від турбоустановки Т-250/300-240 з використанням розроблених засобів.

The technology of problem solving of heat-power station modes optimization with usage of changeable, adapted powerplant models is esteemed. The computational researches of heat tempering modes from turbine T-250/300-240 with usage of designed tools are performed.
The choice of rational modes of heat tempering by the heat power station heating blocks
Keywords: энергоустановки; турбоустановка; сетевая вода; бойлер; теплофикационная установка; отопительный отбор